Let’s work together: Online and synchronous coworking on Twitch to demonstrate the collaborative potential of live-streaming - Buitrago, Álex (2022)
The migration of creators from other platforms and the emergence of new lines of content are contributing to the thematic diversification of Twitch.tv beyond its leadership in gaming. This article explores the potential for collaboration, education, and creation of live-streaming platforms by analyzing the online coworking experience of the JaimeAltozano ‘working room’ on Twitch, launched after the outbreak of the Covid-19 pandemic. An initiative that gathered 222,172 hours worked by the community in three months. Using a mixed methods research design, the experience was studied on the basis of quantitative data, 67 in-depth interviews with users and ethnographic techniques for content analysis. The results obtained in the three phases of the research process show that experiences like the JaimeAltozano ‘working room’ are useful virtual spaces for productivity. Based on these results, a map of the phenomenon was drawn using six key concepts: gamification, synchronicity, community, participation, free operability, and common atmosphere. In the face of the growing platformization of cultural goods, our research delves into the media reality of Twitch beyond videogaming to explore the possibilities of live-streaming for the digital community’s media empowerment.